PENGARUH DJAMALUDDIN ADINEGORO DALAM PERKEMBANGAN PERS MASA KOLONIAL BELANDA (1932-1942) - Roro Ajeng Apriyani, Roro Ajeng Apriyani (Program Studi Pendidikan Sejarah - Universitas Samudra, 2022)
This study aims to examine the background of Djamaluddin Adinegoro's entry into the Indonesian press movement and to examine the contents of Djamaluddin Adinegoro's writings against the Dutch colonial government in 1932-1942. The method used in this research is a qualitative research method where data collection is carried out through a historical approach. Based on the results of the study, it is shown that Djamaluddin Adinegoro's writings have succeeded in giving birth to a separate political awareness for the Indonesian people, to be more advanced and not easily fooled by lack of information. The great influence of reading Djamaluddin Adinegoro's writings is able to guide Indonesian youth in national awareness and stimulate the birth of the spirit of the Indonesian national movement in the 20th century. Adinegoro's actions should be a mirror for young Indonesian journalists today. The writing produced must have a use value that is useful for every reader. It does not only increase knowledge but also becomes a tool for growing awareness of the spirit of nationalism for Indonesian youth.